The CREATE strategy of rehabilitation and recovery for mental illness in low resource settings: Development processes and evaluation from a proof of concept study in Kenya. Issue 1 (2nd January 2022) - MacDougall, Arlene G.; Krupa, Terry; Lysaght, Rosemary; Mutiso, Victoria; Casey, Regina; Le Ber, Marlene J.; Ruhara, Ruth; Price, Elizabeth; Kidd, Sean; Ndetei, David M.
Abstract: A significant burden and treatment gap associated with serious mental illness (SMI) exists in low- and middle-income countries (LMIC). In order to address these issues, a range of community-based rehabilitation models in alignment with the Capabilities Approach is necessary, including opportunities for people with SMI to be rapidly engaged in meaningful work within their communities. This paper outlines the development processes and evaluation of the proof of concept for the Community REcovery Achieved Through Entrepreneurship (CREATE) strategy in Kenya. The CREATE strategy pairs Work Integration Social Enterprises (WISE) with a focused, low-cost, recovery-oriented Psychosocial Rehabilitation (PSR) toolkit within a peer involvement/support model as a means of addressing marginalization and fostering health, wellbeing, and participation of people living with SMI. Qualitative research methods were used to understand the experiences of a range of stakeholders involved in CREATE implementation in Kenya. Three overarching themes explicated the experiences of the various stakeholders involved: (1) experiencing a business like other businesses – yet different; (2) expanding capacities, opportunities, and networks through meaningful work; and (3) promoting knowledge and empowerment through education. Within each theme, there was evidence of the attenuation of central elements of marginalization. The CREATE strategy demonstrated acceptability and a variety of potential positive impacts in a low resource setting in Kenya. Application of the CREATE strategy to other low resource settings within Kenya and other LMIC merits further exploration.